Polymers based on renewable raw materials - Jovanović Slobodan M.; Stojanović Željko P.; Jeremić Katarina B. (Hemijska Industrija, 2002)
The basic raw materials for the chemical industry, which also means for polymer production, are mineral oil and natural gas. Mineral oil and natural gas resources are limited so that sooner or later they will be consumed. For this reason alternative, renewable raw materials for the chemical industry have become the object of intensive investigation all over the world. Some of the results of these investigations concerning renewable raw materials for the production of polymer materials are presented in this paper.